2021
DOI: 10.3390/nano11112846
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Cycloalkanes over N-Doped Carbon-Supported Catalysts: The Effects of Active Component and Molecular Structure of the Substrate

Abstract: Efficient dehydrogenation of cycloalkanes under mild conditions is the key to large-scale application of cycloalkanes as a hydrogen storage medium. In this paper, a series of active metals loaded on nitrogen-doped carbon (M/CN, M = Pt, Pd, Ir, Rh, Au, Ru, Ag, Ni, Cu) were prepared to learn the role of active metals in cycloalkane dehydrogenation with cyclohexane as the model reactant. Only Pt/CN, Pd/CN, Rh/CN and Ir/CN can catalyze the dehydrogenation of cyclohexane under the set conditions. Among them, Pt/CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Besides, side reactions like coke formation and dealkylation were observed at high temperatures (>350 °C) [243]. A series of noble metal catalysts supported on nitrogen-doped carbon showed that Pt was the most active catalyst, with the activity order Pt > Pd > Rh > Ir [244]. Extensive study of Pt supported on metal oxides and perovskites showed that 1 wt.% catalysts were more efficient than 3 wt.% catalysts, potentially due to the smaller size of the Pt nanoparticles [245].…”
Section: Dehydrogenationmentioning
confidence: 99%
“…Besides, side reactions like coke formation and dealkylation were observed at high temperatures (>350 °C) [243]. A series of noble metal catalysts supported on nitrogen-doped carbon showed that Pt was the most active catalyst, with the activity order Pt > Pd > Rh > Ir [244]. Extensive study of Pt supported on metal oxides and perovskites showed that 1 wt.% catalysts were more efficient than 3 wt.% catalysts, potentially due to the smaller size of the Pt nanoparticles [245].…”
Section: Dehydrogenationmentioning
confidence: 99%